Pengaruh Struktur Modal, Ukuran Perusahaan, Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019: Studi Kasus Universitas Indo Global Mandiri - Nabila Rizki Egitasari; Emilia Gustini; R.M. Rum Hendarmin (Journal of Accounting and Taxation, 2023)
The objectives of this study are to analyze the effect of capital structure, company size, profitability on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2015-2019. Data obtained from the company's annual financial statements. The sample in this study amounted to 13 companies. Furthermore, the data were tested using multiple linear regression. The evidence from this study suggests that the capital structure, company size, profitability have a positive effect on the company's stock price. This study is useful for food and beverage companies listed on the Indonesia Stock Exchange to increase their share price. Companies can consider their capital structure, company size, and profitability. Keywords: capital structure, company size, profitability, stock prices, food and beverage companies.